Clinical epidemiological characteristics of traffic injuries in rur alareas - Guryev, S.; Kushnir, V.; Lysun, D.; Kushnir, H. (TERRA ORTHOPAEDICA, 2023)
Summary. Road traffic injury remains one of the main causes of injury in the developing countries, although this is also painful in the developed countries. Even there, providing medical care to road accident victims in rural areas is still a challenge.The aim of the research: to determine and form the clinical and epidemiological characteristics of traffic injuries as a medical and social phenomenon in rural areas.Materials and methods: Ananalysis of 315 cases of victims who received damage as a result of traffic accidents in rural areas was carried out.Results and discussion. The main clinical epidemiological characteristics of traffic injuries in rural areas were studied and the presence of essential features of such injuries was established. In rural areas, there is an advantage of the survival rate over the mortality rate in both sex groups in almost the same value – almost 2 times. The dependence of the occurrence of trauma and the outcome of the traumatic process in traffic accident victims on participation in traffic has been proven. Conclusions: 1 An important feature of the clinical epidemiological characteristics of traffic injuries is a very high percentage of people of working age – 71.75%, which is significantly higher than the same indicator in the metropolis – 63.65%. The highest mortality is also observed in persons of working age 31-60 years (36.36%-41.86%).